Fundamentals of Entrepreneurship (ENT300) Business Plan : Washoku Café / Muhammad Shazrul Hafizam Moestaffa - Moestaffa, Muhammad Shazrul Hafizam (2020)
Washoku Café, is a Japanese Café that establish in Ipoh, Perak that provided variety of Japanese Food. The main purpose of the Washoku Café is to fulfil the demand of Japanese Food in Ipoh, Perak. This because, in Ipoh Perak there only have couple of Japanese Café and it quite expensive for the them. Because of that, we at Washoku Café were trying our best to provide the consumer with the lowest price compared to the others Japanese Café. At Washoku Café, we will provide variety of Japanese Food from the Traditional to the modern food such as sushi, ramen, soba, and the others. The consumer in Ipoh will be able to experience the real taste of Japanese Food same as sell in Japan. This is because, normally the consumer in Malaysia were not be able to travel and try the food in Japan because of the cost to travel is quite expensive. Because of that problem, I determine to open the Washoku Cafe at Ipoh, Perak. At Washoku Cafe, we try our best to provide the best traditional and modern Japanese food to the consumer in Ipoh and all the material that we being used were import all the way from Japan. By using the material from Japan, we will make sure our food is guarantee 100 percent will be taste same as Food that sold in Japan. Besides that, our main target customer is who have an interest with the Japanese Culture. This is because, at Washoku Café we will make sure that our customer will be experience the Japanese food with the vibes same as in Japan. Our café interior design is will be that same as in the Japan and we believe our customer will love it. Beside that it has a term for the person who are really interest with Japanese Culture which is been called as Japanophilia. Japanophilia is the appreciation and love of Japanese culture, people and history. Normally, today people being influence the Japanese Culture by the anime and manga fandom. At our Café, they will be able to experience the food same shows in Anime in order to satisfy their wants. Statistic have been shown that, the potential customer for Japanese food were normally from middle aged and young generation. This is because, the young generation were always desire and willing to experience the culture and things likes try the others country food. The young generation normally were exposed with the internet because of that they always have a little bit of knowledge about others country in terms of food. Washoku Café, target customer was from young generation, caused this generation were always influence by the internet and desire to try new experience of food compared to the older generation. Older generation were tending to like their normal kind of food such like Malaysian National Dishes and they don’t have any intention to try new types of food example Japanese Food. At our café, we will provide variety of Japanese dishes and it will be taste same as in Japan. At Washoku Café, we are served good and a variety of choices Japanese food with a lower price compared to the others Japanese café in Ipoh, Perak. There are few Japanese Café in Ipoh but we are trying to compete with them such as Sushi King. As our concern, we trying our best to give the lowest price compared to the others. Normally, Japanese food were quite expensive and the food were not worth it to try. Because of that, Washoku Café served the food with the lowest price than others and our main concern is to make sure all of our customer are fully satisfy with our food and services. Back in the day, people are not able to experience and buy the Japanese caused it too expensive but now say no more.